Cross perspective person re-identification (drone and ground cameras) - Carmon, Daniel (Nanyang Technological University, 2024)
Person Re-Identification (Person Re-ID) is a challenge which main goal relates to the matching of person images obtained from various cameras. Person Re-ID is growing in importance in several key fields relating to homeland security, surveillance, and sports performance. Cross Perspective Person Re-ID delves specifically into when the matching of person images when the images are gathered at different viewpoints from one another. Currently datasets linked to Person Re-ID do not consider issues within the cross-perspective realm. As it is primarily focused on recognising people from a similar vantage point.